Tacrolimus Rescue Therapy for Corticosteroid-Resistant and Polyclonal Antibody-Resistant Kidney Allograft Rejections - Naderi, Gholam Hossein; Mehraban, Darab; Ganji, Mohammad Reza; Yahyazadeh, Seyed Reza; Latif, Amir Hossein (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; span.bibrecord-highlight1 mso-style-name:bibrecord-highlight1; color:#CC0000; font-weight:bold; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The conventional treatment of acute kidney allograft rejection consists of high-dose corticosteroids and polyclonal antibodies. We report our experience of tacrolimus rescue therapy in patients with acute rejections refractory to corticosteroids and polyclonal antibodies. Materials and Methods: A total of 34 patients with a mean age of 42.3 years and clinical diagnosis of acute kidney allograft rejection underwent tacrolimus rescue therapy when treatment with corticosteroids and polyclonal antibodies failed. Kidney allograft biopsy results were available in 21 patients. All of the patients received tacrolimus, 0.1 mg twice daily, and in those who responded to the therapy after 4 to 6 months, tacrolimus was changed into cyclosporine. Results: Pathologic examination of 21 biopsy specimens of the kidney allografts showed acute vascular rejection in 7 patients (33.3%), acute humoral rejection in 6 (28.6%), acute cellular rejection in 3 (14.3%), and accelerated acute rejection in 3 (14.3%). Twenty-six patients (76.5%) responded to rescue therapy with tacrolimus and discharged with a mean serum creatinine level of 1.4 mg/dL (range, 1.1 mg/dL to 1.7 mg/dL). Allograft nephrectomy was done in 8 patients (23.5%) because of no response to treatment of rejection, the pathology reports of which consisted of acute vascular rejection in 5 patients and extensive necrosis in 3. Conclusion: Tacrolimus therapy is able to salvage kidney allografts with acute refractory rejection. We recommend that tacrolimus be used as an alternative to the conventional drugs used for antirejection therapy. However, severe infectious complications as a result of overt immunosuppression must be considered.